Students Mathematical Communication Ability On Transformation Geometry - Imami, Adi Ihsan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
The purpose of this study was to determine the level of mathematical communication ability of high school students in the subject of transformational geometry. The population in this study were students of class XI at one of senior high school in Karawang. The sample selection was carried out by means of purposive sampling. This study uses a qualitative descriptive approach, with analytical techniques: (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this study are that students' mathematical communication abilities on transformation geometry material in one of the high school schools in Karawang district are in the sufficient category with an average value of 49%. One indicator of communication skills that should get more attention is the ability of students to connect real events or the application of mathematics to everyday life in the form of mathematical ideas.